(untitled) (Journal of the College of Basic Education, 2022)
The importance of this rule has emerged at the present time, because this term is frequently used in political and monarchical regimes without the existence of studies and research that clearly stand on the meaning of the adjacent signature. Is this rule fixed in most constitutions?Or the significance of the adjacent signature.In general, the adjacent signature rule requires appending some of the most important decisions with two signatures, one of which is for the head of state and the other for the head of government. Or one of them is for the prime minister and the other for a minister of his government. But what is the point of having the adjacent signature? In which decision does the constitution require that the two signatures be twinned?